2013
DOI: 10.3389/fneng.2013.00007
|View full text |Cite
|
Sign up to set email alerts
|

The blood-brain barrier: an engineering perspective

Abstract: It has been more than 100 years since Paul Ehrlich reported that various water-soluble dyes injected into the circulation did not enter the brain. Since Ehrlich's first experiments, only a small number of molecules, such as alcohol and caffeine have been found to cross the blood-brain barrier, and this selective permeability remains the major roadblock to treatment of many central nervous system diseases. At the same time, many central nervous system diseases are associated with disruption of the blood-brain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
495
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(515 citation statements)
references
References 271 publications
(425 reference statements)
7
495
0
13
Order By: Relevance
“…32 Due to the limited volume and diffusion constraints of the ECS, the local neuronal K þ efflux (e.g., occurring during the repolarization phase of action potentials) is sufficient to significantly increase ½K þ o . While the basal ½K þ o concentration is ∼3 mM, 33 somewhat lower than the plasma concentration, ½K þ o may rise to 10 to 12 mM during sustained neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
“…32 Due to the limited volume and diffusion constraints of the ECS, the local neuronal K þ efflux (e.g., occurring during the repolarization phase of action potentials) is sufficient to significantly increase ½K þ o . While the basal ½K þ o concentration is ∼3 mM, 33 somewhat lower than the plasma concentration, ½K þ o may rise to 10 to 12 mM during sustained neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
“…This is clearly one mechanism underpinning the adverse effect of neuroinflammation and oxidative stress on iron accumulation in the CNS. Several authors have also reported that upregulation of divalent metal transporter 1 (DMT1) on the surface of neurones and glial cells results from the release of TNF-α, IL-1β, IL-6 and NO by LPS-activated microglia [330][331][332]. Importantly, the release of PICs from activated microglia, most notably IL-6, also leads to increases of hepcidin and reduction of ferroportin in neurones, which supplies a mechanism allowing increasing Fig.…”
Section: Transcriptional Regulation Of Iron Homeostasismentioning
confidence: 99%
“…Once in the cytosol, Fe(II) can be utilised for various essential metabolic processes such as the synthesis of iron-sulphur proteins, or sequestrated by cytosolic ferritin and mitochondrial ferritin (FtMt), which offers protection against the advent of the Fenton reaction. Iron is removed from neurones by ferroportin, supported by the multi-coppercontaining ferroxidase caeruloplasmin and sAPP, which both act to stabilise ferroportin at the cell surface levels of neuronal iron accumulation over time in an environment of neuroinflammation [330,331,333].…”
Section: Transcriptional Regulation Of Iron Homeostasismentioning
confidence: 99%
“…The BBB is a specialized system of capillary endothelial cells which are partially covered by pericytes and basement membrane is almost fully surrounded by the end feet of astrocytes preventing approximately 98% of the small molecules and nearly 100% of large molecules from being transported into the brain [2,3]. The BBB strictly limits drug transport into the brain by serving as a physical, metabolic and immunological barrier.…”
Section: Introductionmentioning
confidence: 99%